Postoperative Care Navigation for Total Knee Arthroplasty Patients: A Randomized Controlled Trial. Issue 9 (28th July 2016) - Losina, Elena; Collins, Jamie E.; Wright, John; Daigle, Meghan E.; Donnell‐Fink, Laurel A.; Strnad, Doris; Usiskin, Ilana M.; Yang, Heidi Y.; Lerner, Vladislav; Katz, Jeffrey N.
Abstract : Objective: To establish the efficacy of motivational interviewing–based postoperative care navigation in improving functional status after total knee arthroplasty (TKA) and to identify subgroups likely to benefit from the intervention. Methods: We conducted a parallel randomized controlled trial in TKA recipients with 2 arms: postoperative care with frequent followup by a care navigator or usual care. The primary outcome was the difference between the arms in Western Ontario and McMaster Universities Osteoarthritis Index function score change, over 6 months postsurgery. We performed a preplanned subgroup analysis of differential efficacy by obesity and exploratory subgroup analyses on sex and pain catastrophizing. Results: We enrolled 308 subjects undergoing TKA for osteoarthritis. Mean ± SD preoperative function score was 41 ± 17 (0–100 scale, where 100 = worst function). At 6 months, subjects in the navigation arm improved by mean ± SD 30 ± 16 points compared to 27 ± 18 points in the usual‐care arm ( P = 0.148). Participants with moderate to high levels of pain catastrophizing were unlikely to benefit from navigation compared to those with lower levels of pain catastrophizing ( P = 0.013 for interaction). Conclusion: Subjects assigned to the navigation intervention did not demonstrate greater functional improvement compared to those in the control group. The negative overall result could be explained by the large effect on functional improvement of TKA itself compared to the smaller, additional benefit from care navigation, as well as by potential differential effects for subjects with moderate to high degrees of pain catastrophizing. Greater focus on developing programs for reducing pain catastrophizing could lead to better functional outcomes following TKA.